Strategic stability in a new era - Paul J. Bolt (Frontiers in Political Science)
Numerous factors are undermining strategic stability in the contemporary world, making the prospects of nuclear war more dangerous. This article reviews the concept of strategic stability and provides an overview of the nuclear forces of the United States, Russia, and China to offer some understanding of the nuclear hardware that shapes strategic stability. It next explores new challenges to strategic stability. These include uncertainty about the reasoning behind China’s nuclear buildup and the strategic challenge this buildup presents to the United States, the shift to a tripolar nuclear “balance” as China’s nuclear forces continue to grow, Russian threats to use nuclear weapons in Ukraine, enhanced Russian-Chinese ties overall and specifically in the nuclear arena, and challenges posed by smaller nuclear powers. The article concludes by discussing important implications of changes in the strategic environment and hence strategic stability. These include pressures on the United States to upgrade its nuclear posture, greater challenges for the US in convincingly providing extended deterrence to its allies, and the need to shift focus in arms control from limiting the number of weapons to more modest but achievable goals.